Parenting Style and Social Media Exposure on Bullying Behavior of Rural Adolescents - Puji Hadiyanti; Daddy Darmawan; Intan Dewi; Bayu Pradikto; Setiawan Wibowo; Lei Wanpeng (Universitas Negeri Semarang, 2026)
Background: Bullying among adolescents remains a serious social problem in Indonesia, including in rural areas experiencing rapid digitalization. Parenting styles and increasing exposure to social media are key factors influencing aggressive behavior and bullying among adolescents. Research Objectives: This study aims to analyze the influence of parenting styles and social media exposure on bullying behavior among adolescents in Sukaharja Village, Bogor Regency. Research Method: This study employed an explanatory quantitative approach with a cross-sectional design. A total of 245 adolescents aged 12–18 years were selected using stratified random sampling. Data were collected through structured questionnaires and analyzed using Pearson correlation and multiple linear regression. Research Findings: The results show that parenting style has a significant negative effect on bullying behavior, while social media exposure has a significant positive effect. The regression model explains 35.4% of the variance in adolescent bullying behavior, with age and gender also showing significant influence. Conclusion: Positive and authoritative parenting combined with parental guidance in social media use plays a crucial role in reducing bullying behavior among rural adolescents. Novelty/Originality/Value: This study provides empirical evidence on the combined influence of parenting styles and social media exposure on bullying behavior in a rural Indonesian context, offering a holistic perspective for family- and community-based bullying prevention strategies.